The Late Poetry of Manuel Álvarez Ortega from the Fragments of Heraclitus. A Hermeneutic Proposal (XXI Century. Spanish Literature and Culture, 2024)
The late poetry of Manuel Álvarez Ortega (Córdoba, 1923 - Madrid, 2014) can be approached from its proximity to some of the formulas found in the fragments of Heraclitus. All this in accordance with a dialectic that, in the Cordovan author, is perpetuated as a drift that, in its way, leaves behind a universe of disubstantiated forms. A study of Álvarez Ortega's late works - alluding to the collections of poems Cenizas son los días (Devenir, 2011) and Ultima necat (Abada, 2012) - from Heraclitean foundations allows us to establish a way of access to a changing and, at times, contradictory poetic thought.
Keywords: Manuel Álvarez Ortega; Contemporary Spanish poetry; Heraclitus; Comparative literature